Maltodextrina em rações de leitões desmamados com diferentes pesos: Desempenho e morfometria intestinal - Augusto, Regina Maria Nascimento [UNESP]; Berto, Dirlei Antonio [UNESP]; Lo Tierzo, Vivian [UNESP]; De Mello, Gabriela [UNESP]; Hauptli, Lucélia [UNESP]; Lucchesi, Lauro [UNESP] (Universidade Estadual de Maringa, 2011)
Two trials were conducted: in the first trial, 96 weaning pigs at the age of 21 days were used, in a block design, with a 2 x 2 factorial arrangement (two sources of carbohydrate and two weaning weight classes). In the second trial, 48 pigs were used, in a block design, with 2 x 2 x 2 x 3 factorial arrangement (two weaning weight classes x two sources of carbohydrate x two portions of the small intestine x three slaughter periods). The effects of the replacement of lactose by maltodextrin in diets of weaning pigs, with different weights, were evaluated on daily feed intake, daily weight gain, feed:gain ratio, villus height, crypt depth and thickness of the mucosa. In the first trial, from 0 to 17 days and from 0 to 29 days after weaning, effects of weight classes were detected on daily weight gain and daily feed intake. In the second trial, maltodextrin resulted in an increase in the average thickness of the intestinal mucosa and in average crypt depth, only in lighter animals. Maltodextrin can be used as an alternative to lactose in diets of weaning pigs.
Maltodextrin in diets for weaning pigs of different weights: Performance and intestinal morphometry
Keywords: Depth of the crypt; Lactose; Thickness of the mucosa; Villi height; Animalia; Suidae